Alterations of Gut Microbiome and Fecal Fatty Acids in Patients With Polycystic Ovary Syndrome in Central China - Li, Gailing; Liu, Zhenguo; Ren, Fang; Shi, Huirong; Zhao, Qian; Song, Yi; Fan, Xunjie; Ma, Xiaojun; Qin, Guijun (Frontiers in Microbiology, 2022)
Objective: The purpose of this study was to elucidate the characteristics of the gut microbiome in patients with Polycystic ovary syndrome (PCOS) and analyze the alterations of fecal fatty acid metabolism, so as to further provide the pathogenesis of PCOS. Methods: Fecal samples from the PCOS group (n=31) and healthy control group (n=27) were analyzed by 16S rRNA gene sequencing and untargeted metabolomics. Peripheral venous blood was collected to measure serum inflammation and intestinal permeability. Finally, the correlation analysis of intestinal flora, fecal metabolites, and laboratory indicators was carried out. Results: Serum D-lactate content in the PCOS group was higher than that in the control group. There was no significant difference in microbial α diversity and β diversity between PCOS patients and healthy controls. Peptostreptococcaceae and Bacteroidales S24-7 group existed significant differences between PCOS patients and healthy controls. Based on linear discriminant analysis selection, 14 genera including Klebsiella, Enterobacteriaceae, and Gammaproteobacteria were dominant in patients with PCOS, while 4 genera, including rumenococcus (Ruminocaccaceae UCG 013), prewortella (Prevotellaceae UCG 001), and erysipelas (Erysipelatoclostridium), were dominant in healthy controls. Compared with PCOS with Body mass index (BMI)<24, patients with BMI≥24 have multiple dominant genera including Abiotrophia and Peptostreptococcaceae. Moreover, serum levels of free testosterone and androstenedione were positively correlated with Megamonas, while total testosterone was negatively correlated with Alistipes. Additionally, fecal contents of acetic acid and propionic acid in patients with PCOS were significantly higher than those in healthy controls. Eubacterium_coprostanoligenes_group and Alistipes were positively correlated with 6 kinds of fatty acids. Conclusion: Specific intestinal flora fecal fatty acids and serum metabolites may mediate the occurrence and development of PCOS. PCOS patients with different body sizes have specific intestinal flora.